2008
DOI: 10.1002/joc.1663
|View full text |Cite
|
Sign up to set email alerts
|

An automated sea breeze selection technique based on regional sea‐level pressure difference: WeMOi

Abstract: ABSTRACT:A recently defined regional teleconnection pattern for the western Mediterranean basin (western Mediterranean Oscillation, WeMO) has allowed an objective quantification of the synoptic circulation factor on the occurrence of sea breezes. The associated WeMO index (WeMOi) can be used as an initial objective filter for selecting ideal surface pressure conditions for sea breeze development. Applying this filter to the sea breeze database created for Alicante (reference synoptic station) and performing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…A number of studies have been conducted on sea–land breezes in the Middle East and North African (MENA) region using both observations and models. Most of these studies have been focused on the Mediterranean Sea, describing the main characteristics of the sea breeze in different regions (Ramis and Alonso, ; Furberg et al, ; Azorin‐Molina and Lopez‐Bustins, ; Azorin‐Molina et al, ; Azorin‐Molina et al, ). Saaroni et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been conducted on sea–land breezes in the Middle East and North African (MENA) region using both observations and models. Most of these studies have been focused on the Mediterranean Sea, describing the main characteristics of the sea breeze in different regions (Ramis and Alonso, ; Furberg et al, ; Azorin‐Molina and Lopez‐Bustins, ; Azorin‐Molina et al, ; Azorin‐Molina et al, ). Saaroni et al .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted on sea-land breezes in the Middle East and North African (MENA) region using both observations and models. Most of these studies have been focused on the Mediterranean Sea, describing the main characteristics of the sea breeze in different regions (Ramis and Alonso, 1988;Furberg et al, 2002;Azorin-Molina and Lopez-Bustins, 2008;Azorin-Molina et al, 2009a;Azorin-Molina et al, 2011). Saaroni et al (2004) noted a weaker pressure gradient (38% less than the average) on sea breeze days in the Gulf of Aqaba and also found that sea breeze events occurred on only 25% of the days in July and August during a 6-year study period and lasted 4-6 hr.…”
mentioning
confidence: 99%
“…For example, the urban heat island (UHI) effect can cause increasing temperature gaps between sea and land, leading to strengthened SLB circulation (Ma et al, 2013). In addition to model simulation studies, there have also been many observational studies that investigated the structure of SLBs (Oliphant et al, 2001), particularly during the recent period when high time‐resolution observational data have been available for coastal cities worldwide (Azorin‐Monica & Lopez‐Bustins, 2008; Finkele et al, 1995; Park & Chae, 2018). Finkele et al (1995) used high‐resolution data to reveal the three‐dimensional structure of SLB circulation in the coastal areas of South Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The most common meteorological framework during the summer months over the Western Mediterranean coast is that corresponding to mesoscale circulations associated with sea-land breezes (Azorin-Molina et al, 2008;Azorin-Molina et al, 2009;Miró et al, 2009;Azorin-Molina et al, 2011), which assumes more than 80% of the situations over eastern Spain (Miró et al, 2009). However, those atmospheric conditions connected to western synoptic advections are also recognized in this region as they are related to high and extreme temperature situations, specially inland but reaching the coast as well (Miró et al, 2006;Estrela et al, 2007;Estrela et al, 2008).…”
Section: Introductionmentioning
confidence: 99%